Cholinergic system in sleep regulation of emotion and motivation. (May 2019) - Mu, Ping; Huang, Yanhua H.
Abstract: Sleep profoundly regulates our emotional and motivational state of mind. Human brain imaging and animal model studies are providing initial insights on the underlying neural mechanisms. Here, we focus on the brain cholinergic system, including cholinergic neurons in the basal forebrain, ventral striatum, habenula, and brain stem. Although much is learned about cholinergic regulations of emotion and motivation, less is known on their interactions with sleep. Specifically, we present an anatomical framework that highlights cholinergic signaling in the integrated reward-arousal/sleep circuitry, and identify the knowledge gaps on the potential roles of cholinergic system in sleep-mediated regulation of emotion and motivation. Sleep impacts every aspect of brain functions. It not only restores cognitive control, but also retunes emotional and motivational regulation [1 ]. Sleep disturbance is a comorbidity and sometimes a predicting factor for various psychiatric diseases including major depressive disorder, anxiety, post-traumatic stress disorder, and drug addiction [2–9 ]. Although it is well recognized that sleep prominently shapes emotional and motivational regulation, the underlying neural mechanisms remain elusive. The brain cholinergic system is essential for a diverse variety of functions including cognition, learning and memory, sensory and motor processing, sleep and arousal, reward processing, and emotion regulation [10–14 ]. Although cholinergic functions in cognition, learning and memory, motor control, and sleep and arousal have been well established, its interaction with sleep in regulating emotion and motivation has not been extensively studied. Here we review current evidence on sleep-mediated regulation of emotion and motivation, and reveal knowledge gaps on potential contributions from the cholinergic system.